Region wise referrals to a tertiary care centre: a retrospective analysis - Paidi, Sirisha; Thonangi, Aashritha (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2019)
Background: Emergency obstetric care in health care requires a linked referral system to be effective in reducing maternal morbidity and mortality. This review is aimed at summarizing the proportion of referrals from urban, rural and tribal areas of surrounding districts to tertiary care centre, King George Hospital, Visakhapatnam for a 6 month period; from May 2018 to October 2018. Methods: Retrospective study done at a tertiary care teaching hospital, including 3157 cases referred from the surrounding urban, rural and tribal areas. Results: Out of the 3157 referred cases, most of them (1658) were from rural areas, 1030 from urban and 469 from tribal areas. Referrals done in view of post caesarean pregnancies were more in urban and rural areas whereas more preeclampsia and anaemia cases were referred from tribal areas. Various indications of referral are documented. Majority of them were unbooked cases. Conclusions: Specific guidelines regarding whom to refer, how to refer and when to refer would be helpful in making timely referral. These would also help to decrease the burden on the tertiary care centers which deal with a huge caseloads in spite of limited infrastructure and manpower. Adequate attention and better care can be given to complicated cases if the total case load is reduced. Stringent documentation in referral slip and better co-ordination are required for a strong health care system.